Highly antibacterial polypeptide-based amphiphilic copolymers as multifunctional non-viral vectors for enhanced intracellular siRNA delivery and anti-infection. (August 2017) - Zhou, Li; Xi, Yuewei; Yu, Meng; Wang, Min; Guo, Yi; Li, Peng; Ma, Peter X.; Lei, Bo
Graphical abstract: Abstract: For next-generation regenerative medicine and cancer therapy applications, the development of multifunctional biodegradable biomaterials with good antibacterial activity, biocompatibility and gene delivery capability is showing increased interests. As a natural cationic polypeptide, poly(ε-l -lysine) (EPL) has been as attractive antibacterial agent and non-viral gene vectors, however, its gene therapy is still limited probably due to the cytotoxicity, low stability in physiological environment and poor transfection efficiency. Herein, series of EPL-based amphiphilic copolymers composed of polyethylene glycol- block -poly(3-hydroxybutyrate- co -4-hydroxybutyrate)- block -EPL (PEG- b -P3/4HB- b -EPL, EHE) was synthesized and evaluated for siRNA delivery and anti-infection applications. EHE copolymers could effectively condense siRNA, protect it from degradation by nucleases and easily release the siRNA under heparin competition. The EHE2 copolymer displayed a good hemocompatibility, significantly high siRNA loading ability (N/P ratio of 1.5–3.0) and lower cytotoxicity compared to commercial branched polyethyleneimine (PEI 25 kDa) and EPL, efficient cellular uptake of siRNA in MCF-7 cells. Additionally, EHE2 copolymers-mediated siRNA delivery revealed a significantly over 3 times high target gene silencing efficiency (62%) as compared to PEI (22%) and EPL (15%) in MCF-7 cells. The EHE2/siRNA also showed better capability than PEI/siRNA complex to drastically reduced VEGF mRNA level down to 46% in A549 cells. Furthermore, EHE copolymers exhibited excellent antimicrobial activity towards positive bacteria ( S. aureus ) in vitro and in vivo . The high gene transfection efficiency, low cytotoxicity and excellent antibacterial activity make EHE polymers highly promising applications in multifunctional gene therapy. Statement of significance: This paper reports a highly antibacterial polypeptides-based EHE copolymer for enhancing siRNA delivery and anti-infection applications. The EHE copolymer displayed a good hemocompatibility, significantly high siRNA loading ability and lower cytotoxicity compared to commercial branched polyethyleneimine (PEI 25 kDa) and EPL, efficient cellular uptake of siRNA in various cancer cells. Additionally, EHE2 copolymers-mediated siRNA delivery revealed a significantly over 3 times high target gene silencing efficiency (62%) as compared to PEI (22%) and EPL (15%) in MCF-7 cells. Furthermore, EHE copolymers exhibited excellent antimicrobial activity towards positive bacteria ( S. aureus ) in vitro and in vivo . The high gene transfection efficiency, low cytotoxicity and excellent antibacterial activity make EHE polymers highly promising applications in multifunctional gene therapy.